Reading job intertextually - Dell, Katharine (Bloomsbury Publishing, 2012)
A comprehensive collection of intertextual readings of the book of Job in connection with texts across the Hebrew Bible and throughout history
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Bibel / Altes Testament; Intertextualität; Bibel / Ijob